Leaping to Diagnosis: The Frog Sign as a Key Clue in AVNRT - Andreas Mussigbrodt; Maria Herrera Bethencourt; Romain Vergier; Marinela Blidar; Alberto Alfie (Clinical Case Reports)
ABSTRACT The “frog sign,” characterized by prominent cannon A waves, is a critical diagnostic clue for AV‐nodal reentrant tachycardia (AVNRT). It was confirmed through electrophysiological study and was successfully treated with radiofrequency ablation.